2015
DOI: 10.1002/9780470559277.ch150099
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Ubiquitin Chains

Abstract: Chemical synthesis of complex biomolecules such as proteins is a challenging adventure, yet rewarding in driving various biochemical and biophysical research activities. Over the years, the refinement of peptide synthesis and invention of ligation methodologies have led to the successful synthesis of several complex protein targets. Ubiquitin bioconjugates, which are being studied intensively by many groups due to their involvement in numerous biological processes, represent a fine example where chemistry is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…42−44 For example, our group found that the use of HCTU/DIEA and three dipeptide building blocks (Ile13-Thr14, Asp52-Gly53, and Leu56-Ser57) were sufficient to achieve a very good synthesis of the various Ub analogues for the synthesis of more complex conjugates. 45 To synthesize the Ub-thioester, one approach is to assemble the Ub sequence with N-methylated Cys at the C-terminus. The N-methylcysteine is utilized as an N → S acyl transfer device for the thioesterification step carried out at pH 1 in the presence of an excess of an alkylthiol such as mercaptopropionic acid (MPA).…”
Section: Chemical Synthesis Of Ub Building Blocksmentioning
confidence: 99%
See 3 more Smart Citations
“…42−44 For example, our group found that the use of HCTU/DIEA and three dipeptide building blocks (Ile13-Thr14, Asp52-Gly53, and Leu56-Ser57) were sufficient to achieve a very good synthesis of the various Ub analogues for the synthesis of more complex conjugates. 45 To synthesize the Ub-thioester, one approach is to assemble the Ub sequence with N-methylated Cys at the C-terminus. The N-methylcysteine is utilized as an N → S acyl transfer device for the thioesterification step carried out at pH 1 in the presence of an excess of an alkylthiol such as mercaptopropionic acid (MPA).…”
Section: Chemical Synthesis Of Ub Building Blocksmentioning
confidence: 99%
“…The distal Flag-Ub-thioester was prepared using N-methylcysteine approach, while the other two Ubs having the same functionalities were prepared by using the MeNbz chemistry, followed by switching the C-terminus to hydrazide and deprotecting the δ-mercaptolysine. 45 Having the Ub building blocks in hand, we assembled the Tri-Ub-thioester chain by taking advantage of the stability and tunability of the hydrazide moiety. First, we performed the ICL between Flag-Ubthioester and Ub hydrazide bearing free δ-mercaptolysine.…”
Section: Chemical Synthesis Of 472 Amino Acid Tetra-ub-α-globinmentioning
confidence: 99%
See 2 more Smart Citations